In situ wear test of acrylonitrile butadiene rubber in a low pressure hydrogen environment - Byeong-Lyul Choi; Myung-Chan Choi; Sang Koo Jeon; Un bong Baek; Byoung-Ho Choi (Polymer Testing)
Polymers are increasingly being used in hydrogen environments because of their potential for high durability and cost-effectiveness in applications such as fuel cells and hydrogen storage systems. However, the interactions between polymers and hydrogen, particularly under varying pressure conditions, can significantly affect their performance, leading to challenges in material selection and design. Hence, this study investigated the tribological behavior of acrylonitrile butadiene rubber (NBR) in low-pressure hydrogen environments and focused on the effects of different filler types and contents, including carbon black and silica. Using a custom-designed in situ tribometer, wear tests were conducted to evaluate the friction and wear characteristics of the NBR composites in hydrogen, helium, and ambient air atmospheres. The findings indicated that the filler type and content critically influenced the tribological performance of NBR, with carbon black-filled NBR showing higher friction coefficients and wear rates and silica-filled NBR exhibiting superior wear resistance and lower friction. These results emphasize the importance of optimizing the filler selection to enhance the durability and effectiveness of NBR in hydrogen-rich environments. Therefore, the results of this study provide valuable insights for the development of robust sealing materials for hydrogen energy applications.